PENGARUH MOTIVASI, KEDISIPLINAN, KECERDASAN EMOSIONAL, DAN KOMPETENSI MENGAJAR TERHADAP KINERJA GURU SEKOLAH DASAR - Ernawati, Wahyu Kartikasari - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2009)
ABSTRACT Research purposes are (1) to analyze signifincance influence of motivation, discipline, emotional intellegence, and teaching competency to Elementary School Teacher Performance in District Wonosari Sub-province Klaten partially. (2) to analyze significant influence ot motivation, discipline, emotional intellegence, and teaching competency to Elementary School Teacher Performance in District Wonosari Sub-province Klaten together. (3) to analyze the most dominant factor influencing among motivation, discipline, emotional intellegence, and teaching competency to Elementary School Teacher Performance in District Wonosari Sub-province Klaten. Population in this research is entire of Elementary School teacher in District Wonosari Sub-province Klaten, amounts of 417 persons devided into 41 Elementary School, and 4 Dabin. Sample taken as 97 teachers. Sampling taken technique has got by using purposive sampling technique. Data analysis method used double linear regression. This result concludes that discipline is the most dominant factor influencing teacher performance, to improve teacher discipline suggested government accociates the rules, makes teacher awareness to their duties, accustoming teacher to do headmaster comand orally and also written, give construction to teacher about teacher done duties, observation and real action to teacher attendance, observation to atribute and uniform, and improving teacher awareness that they are reference for their students through the headmaster. Keywords: motivation, discipline, emotional intellegence, teaching compentency and teacher performance.